Prolonged lung cancer screening reduced 10-year mortality in the MILD trial: new confirmation of lung cancer screening efficacy - Pastorino, U; Silva, M; Sestini, S; Sabia, F; Boeri, M; Cantarutti, A; Sverzellati, N; Sozzi, G; Corrao, G; Marchianò, A (Annals of oncology, 2019)
Abstract Background The National Lung Screening Trial showed that lung cancer (LC) screening by three annual rounds of low-dose computed tomography (LDCT) reduces LC mortality. We evaluated the benefit of prolonged LDCT screening beyond 5 years, and its impact on overall and LC specific mortality at 10 years. Design The Multicentric Italian Lung Detection (MILD) trial prospectively randomized 4099 participants, to a screening arm (n = 2376), with further randomization to annual (n = 1190) or biennial (n = 1186) LDCT for a median period of 6 years, or control arm (n = 1723) without intervention. Between 2005 and 2018, 39 293 person-years of follow-up were accumulated. The primary outcomes were 10-year overall and LC specific mortality. Landmark analysis was used to test the long-term effect of LC screening, beyond 5 years by exclusion of LCs and deaths that occurred in the first 5 years. Results The LDCT arm showed a 39% reduced risk of LC mortality at 10 years [hazard ratio (HR) 0.61; 95% confidence interval (CI) 0.39–0.95], compared with control arm, and a 20% reduction of overall mortality (HR 0.80; 95% CI 0.62–1.03). LDCT benefit improved beyond the 5th year of screening, with a 58% reduced risk of LC mortality (HR 0.42; 95% CI 0.22–0.79), and 32% reduction of overall mortality (HR 0.68; 95% CI 0.49–0.94). Conclusions The MILD trial provides additional evidence that prolonged screening beyond 5 years can enhance the benefit of early detection and achieve a greater overall and LC mortality reduction compared with NLST trial. ClinicalTrials.gov identifier NCT02837809.